Synthesis of Biodiesel from Ceiba Pentandra using Microwave Assisted Technique - Tan , Meng Kiat (Universiti Teknologi PETRONAS, 2013)
The rapid growth of industrial and human population had encouraged the exploration of renewable fuel such as biodiesel which is produced from plant oil and animal fat. Ceiba Pentandra which is one of the non-edible feedstocks, is much explored in Malaysia for biodiesel production. Biodiesel is usually produced by transesterification process using conventional heating which requires large amount of heat energy and long reaction time. This project studies on Kapok oil methyl ester (KOME) production using microwave assisted technique. Studies have been conducted to investigate the optimum operating conditions for the microwave assisted transesterification of Ceiba Pentandra seed oil including the temperature, catalyst concentration, methanol to oil molar ratio and irradiation time. The optimum operating conditions which result in highest KOME yield (95.6%) are found to be at 55°C, 2 wt% KOH catalyst, 10:1 methanol to oil molar ratio and 3.5 minutes of irradiation time. The microwave synthesis reactor which is able to deliver energy directly to the reactant at molecular level has drastically reduced the reaction time and total energy consumption in the transesterification process. The properties of the biodiesel produced under the optimum conditions are characterized and it shows that the KOME meets the international standard of biodiesel (ASTM 6751 & EN 14214).